Different exercise interventions on quality of sleep in breast cancer survivors—a network meta-analysis of randomized controlled trials - Song, Qi; Zhu, You-kang; Liu, Hai; Liu, Xiao; Jiang, Zhang-dong; Wang, Yu-jia; Xue, Li-yun; Yang, Shao-ying; Liu, Xi-fang (Frontiers in Oncology, 2025)
IntroductionBreast cancer is currently the most prevalent cancer globally; however, it generally has a favorable prognosis and is linked to a high survival rate. While effective treatments can extend survival and mitigate associated side effects, not all survivors are exempt from complications. Notably, a significant proportion of survivors experience sleep disorders following surgery, which can severely impact their quality of life. Exercise is frequently recommended as a non-pharmacological intervention to enhance sleep quality among breast cancer survivors and may also play a role in reducing recurrence rates. Recognizing that various forms of exercise may yield different outcomes in addressing sleep disorders in this population, we conducted a network review meta-analysis to assess the effectiveness of diverse exercise modalities for breast cancer survivors suffering from sleep disturbances.MethodsWe searched four electronic databases for randomized controlled trials of individuals diagnosed breast cancer with sleep disorders by different exercise therapy. The primary outcomes included Yoga, Pilates, Qigong, Tai Chi, Walking, Dance, Resistance training, Football, Virtual reality therapy, Activity change exercise, Software-guided exercises. The methodological quality of the included studies was assessed using the Cochrane Bias risk Assessment tool, and network meta-analysis was performed using Stata15 software. The review was pre-registered (PROSPERO ID: CRD42023442892).ResultsData on 3083 breast cancer survivors with sleep disturbances from 34 eligible randomized controlled trials were analyzed, with 23 classified as medium risk and 2 as high risk. Network meta-analysis showed that walking exercise [Standard Median Different (SMD) =3.06, 95% Confidence Interval (95%CI)=(-5.89,-0.23)] significantly improved sleep disorder (Surface Under the Cumulative Ranking curve, SUCRA: 84.5%) and reduced Pittsburgh sleep quality index (PSQI) score.DiscussionBased on the network ranking table, we can conclude that walking exercise offers greater benefits compared to other exercise interventions for improving sleep quality in breast cancer patients. This finding presents a novel perspective on exercise interventions for breast cancer survivors experiencing sleep disorders.Systematic review registrationPROSPERO https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=442892, identifier CRD42023442892.